2021
DOI: 10.1155/2021/6632450
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Change Detection Analysis of Coastline Data in Qingdao, East China

Abstract: This study focuses on the coastal features, environments, and dynamics to accurately describe and regularly monitor the Qingdao shoreline in eastern China. It collects categorical ETM+ and OLI data from 2000, 2010, and 2019 on the mainland coastline and explores the characteristics and spatiotemporal differences across the past 19 years by using remote sensing and geographic information system (GIS) technologies. The results show that the length of the Qingdao coastline has increased continuously over the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…The growth of urban fronts in the coastal area resulted this artificial increase of coastline length. For example in Asia, Yasir et al [41] found from 2000 to 2019 a rise of 68% in the length of artificial coastline of Qingdao in East China, compared to the total length of about 500 km. Chee et al [42] found 21 km of artificial coast in a coastline 106 km-long in Penang Island, in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of urban fronts in the coastal area resulted this artificial increase of coastline length. For example in Asia, Yasir et al [41] found from 2000 to 2019 a rise of 68% in the length of artificial coastline of Qingdao in East China, compared to the total length of about 500 km. Chee et al [42] found 21 km of artificial coast in a coastline 106 km-long in Penang Island, in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of high-resolution satellites, the research on coastline extraction based on high-resolution images has also been widely used. Various research scholars have presented many methods for remote sensing interpretation of coastline; the automatic coastline extraction methods such as edge detection (Liu and Jezek, 2004;Sheng et al, 2021), region growth (Jin et al, 2020), threshold segmentation (Wang et al, 2016;Chen et al, 2022), deep learning (Liu et al, 2019), and object-oriented method (Ge et al, 2014;Wu et al, 2015) are used worldwide, while traditional methods, such as the visual interpretation of human-computer interaction, are still widely used by experts to extract coastal information (Yasir et al, 2021). The edge detection, regional growth, and threshold segmentation methods are easily affected by the complex coastal environment, and the type attributes of the coastline cannot be obtained (Yasir et al, 2020;Chang et al, 2021;Yi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bushra et al [21] analyzed multi-temporal satellite images of the Kuakata shoreline from 1989 to 2020 by using remote sensing and the GIS method and concluded that it is an unstable shoreline where both erosion and accretion were taking place over the study period. Yasir et al [22] studied the spatiotemporal of coastline data in Qingdao with Landsat from 2000 to 2019 and found that the coastal zone has increased continuously over the last two decades.…”
Section: Introductionmentioning
confidence: 99%